Strategi Pemasaran Produk Tabungan Siklus Menggunakan Metode Analisis Swot Dalam Meningkatkan Jumlah Nasabah Pada PT. Bank Pembangunan Daerah Jawa Timur Tbk Cabang Kediri - Laksono, Yanis; Nurlaely, Nurlaely; Susyatik, Enni; Rahayu, Budi (Jurnal Ilmiah Raflesia Akuntansi, 2023)
This research aims to identify the product marketing strategy for Siklus Savings to increase the number of customers at PT. Bank Pembangunan Daerah Jawa Timur, Kediri Branch. This type of research is qualitative, which requires answers through literature review and interviews with informants, specifically employees of Bank Jatim, Kediri Branch. The analytical method used is descriptive analysis with a SWOT analysis approach, which is a method of identifying and analyzing existing data to provide a clear picture of the strengths, weaknesses, opportunities, and threats faced by Bank Jatim, Kediri Branch, in increasing the number of customers. From the results of this study, it can be concluded that to increase the number of customers, it is necessary to formulate strategies for selecting and targeting markets using Segmentation, Targeting, and Positioning. The SWOT analysis concludes that the strengths of Bank Jatim include its brand image, strategic location, and government support. The weakness lies in the customers' lack of knowledge about mobile banking. The opportunity for Bank Jatim is its accessible office locations, while the threat is the high number of competitors.